2012
DOI: 10.1016/j.apsusc.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Choice of biomaterials—Do soft occlusal splints influence jaw-muscle activity during sleep? A preliminary report

Abstract: Highlights AbstractAim: The choice of biomaterials for occlusal splints may significantly influence biological outcome. In dentistry, hard acrylic occlusal splints (OS) have been shown to have a temporary and inhibitory effect on jaw-muscle activity, such as tooth clenching and grinding during sleep, i.e., sleep bruxism (SB). Traditionally, this inhibitory effect has been explained by changes in the intraoral condition rather than the specific effects of changes in occlusion. The aim of this preliminary study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…Regarding the increased MBF values of 2 and 3 mm thick hard occlusal splints, the results of this study were in line with those of previous studies evaluating 0.6, 1, 2, and 3 mm thick splints [19,21,36]. The present study also found a signi cant increase in MBF on both sides (right/left) during hard occlusal splint therapy, and this increase may be associated with the positive effect of hard occlusal splints on neurobiological regulation of jaw-muscle activity (Figure -2) [37]. While there is only one study in the literature showing that the use of hard splints (1 mm) reduces MBF in patients with bruxism, there are also studies showing that the use of hard splints does not affect MBF (1.5 mm, 2 mm, 3 mm and 6 mm thick splints) [12,21,24,38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the increased MBF values of 2 and 3 mm thick hard occlusal splints, the results of this study were in line with those of previous studies evaluating 0.6, 1, 2, and 3 mm thick splints [19,21,36]. The present study also found a signi cant increase in MBF on both sides (right/left) during hard occlusal splint therapy, and this increase may be associated with the positive effect of hard occlusal splints on neurobiological regulation of jaw-muscle activity (Figure -2) [37]. While there is only one study in the literature showing that the use of hard splints (1 mm) reduces MBF in patients with bruxism, there are also studies showing that the use of hard splints does not affect MBF (1.5 mm, 2 mm, 3 mm and 6 mm thick splints) [12,21,24,38].…”
Section: Discussionsupporting
confidence: 92%
“…The choice of biomaterial for occlusal splints has a signi cant effect on the neurobiological regulation of jaw muscle activity during sleep, and splint thickness has been reported to play a role in the incidence of SB [14,37]. In this study, the soft splint groups (S2 and S3) showed the lowest PSQI scores among all groups, indicating an improvement in sleep quality with soft splint use (Figure -3).…”
Section: Discussionmentioning
confidence: 62%
“…Hard stabilization splints significantly reduced the number of sEMG high-activity events per hour of sleep. In contrast, soft occlusal splints do not inhibit jaw muscle activity compared to baseline values [ 39 ]. Despite the advantage of a hard splint, soft splints are used to ease implementation and reduce financial costs to the patient [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Além de ser um tratamento conservador e de baixo custo 20 . Placas interoclusais rígidas promovem efeito inibitório da atividade neuromuscular da mandíbula 24 , reduzindo, durante o sono, a quantidade de eventos de contratura muscular.…”
Section: Discussionunclassified